Force–torque intraoperative measurements for femoral shaft fracture reduction. (16th December 2016) - Zhu, Qing; Liang, Bin; Wang, Xingsong; Sun, Xiaogang; Wang, Liming
Abstract: Background: The minimally invasive technique of closed intramedullary (IM) nailing fixation is currently considered the standard of treatment for the operative management of displaced traumatic fractures of the femur, with fracture reduction and repositioning being the first and most important step of the procedure. Skeletal-muscle traction and alignment of the fracture fragments are always performed as individual components of the reduction and repositioning phase of the procedure. Methods: As use of high traction force and repositioning forces and torques can cause additional soft tissue injury, we developed a sensor-based system to monitor these forces and torques during the treatment of diaphyseal fractures of the femur, including the monitoring of traction forces during the entire procedure, from reduction to IM nail implantation and fixation. Results: Based on a local coordinate system localized at the center of the fracture, maximum forces of 203 N along the medial-lateral (X) axis, 517 N along the anterior–posterior (Y) axis and 505 N along the shaft of the femur (Z-axis) were identified, with maximum torques of 16.4 Nm calculated around Y-axis and 38.3 Nm around X-axis. The pressure between the counteraction post and the perineum was also recorded, with magnitudes as high as 523 N being recorded. Excessive forces were identified and the difference in force–torque magnitudes during different stages of the reduction and fixation procedure were calculated. Conclusion: The measurement system provides surgeons with real-time information which can assist them in performing effective repositioning of fracture fragments within safe margins of applied forces and torques.